Woven Stainless-Steel Mesh as a Gas Separation Membrane for Alkaline Water-Splitting Electrolysis - Michael Warwick (Membranes, 2020)
A 316-grade woven stainless-steel mesh membrane was investigated as a gas-separation membrane for alkaline water-splitting electrolysis. Its resistance was measured using electrochemical impedance spectroscopy (EIS) and linear sweep voltammetry (LSV), with the conclusion that it presented approximately half the resistance of a comparable commercial alternative (ZirfonTM). Its gas-separation performance was analysed using gas chromatography (GC) at 140 mA cm−2, where it achieved 99.25% purity at the hydrogen outlet of the electrolyser. This fell to 97.5% under pumped circulation, which highlights that it is sensitive to pressure differentials. Nevertheless, this mixture is still more than a factor two inside the upper flammability limit of hydrogen in oxygen. It is hoped that such a low-cost material may bring entry-level electrolysis to many hitherto discounted applications.